Quail Methodology: Where are We and Where Do We Need to Be? - Dean F. Stauffer (National Quail Symposium Proceedings, 2017)
I review and evaluate methods used for population estimation, determination of survival, radio-tagging, habitat analysis and evaluation, and study design and analysis. I conclude that rigorously designed call-count surveys are likely to provide the best information on quail population trends across time and space. More intensive techniques such as line transects and mark-recapture may be appropriate if the resources are available. Radio-tagging can be a very useful technique; however, in many cases, triangulation error and effects of equipment on the birds may render results suspect. Therefore, caution is urged when using radio-tagging. Approaches to habitat analysis and evaluation are described. I discuss the importance of replication in study design and the use of appropriate and rigorous statistics. I suggest we consider statistical power more in the interpretation of results. Generally, we have the techniques available to meet our needs, but implementation has been less than ideal in many cases. Finally, the dichotomy between researchers and managers needs to be bridged. Better communication of needs by managers and cooperation by researchers should lead to positive results concerning our quail resources.
Keywords: habitat analysis; population estimation; quail; radio-tagging; statistics; study design